Research and Application of Pumping Program Design Software - ZHAO Xindi; YANG Dengbo; LIU Wei; NIE Jingwen; WANG Jian (Cejing jishu)
In the process of unconventional oil and gas resources development, the use of hydraulic pumping for perforating string transportation has always been the main means in the industry. However, the traditional hydraulic pumping program design of perforating string has some problems, such as completely relying on the experience of engineering personnel, unclear stress state of downhole perforating string and low accuracy of pumping program, which lead to high risk and low efficiency of field construction. In order to complete the fine pumping program design in unconventional horizontal well pumping operation, this paper proposes a fine pumping program design software based on the pressure drop calculation formula of eccentric annular clearance flow. By fitting the pressure drop calculation formula of eccentric annular clearance flow with the actual pumping program parameters, the accurate pumping parameters and stress conditions of each pumping stage are obtained. This software obtains accurate pumping parameters and stress conditions at each stage of pumping by fitting the pressure drop calculation formula for eccentric annular gap flow with the actual pumping program parameters on site. Through software engineering design methods, it simulates key construction parameters such as wellbore state, pipe string parameters, pumping speed, thrust resistance parameters, dynamic characteristics of pumped liquid, and pumping displacement step of perforated pipe string during hydraulic pumping in horizontal wells. This software has been promoted in China National Logging Corporation. As of January, 2023, a total of 213 pumping program designs have been completed, with a design compliance rate of 98.2%.